Inhibition of RIP3 increased ADSC viability under OGD and modified the competency of adipogenesis, angiogenesis, and inflammation regulation. Issue 3 (31st March 2022) - Yang, Zhenyu; Qi, Zuoliang; Yang, Xiaonan; Gao, Qiuni; Hu, Yuling; Yuan, Xihang
Abstract: Adipose-derived stem cells (ADSCs) showed decreased cell viability and increased cell death under oxygen-glucose deprivation (OGD). Meanwhile, vital necroptotic proteins, including receptor-interacting protein kinase (RIP) 3 (RIP3) and mixed lineage kinase domain-like pseudokinase (MLKL), were expressed in the early stage. The present study aims to explore the effect of necroptosis inhibition on ADSCs. ADSCs were obtained from normal human subcutaneous fat and verified by multidirectional differentiation and flow cytometry. By applying cell counting kit-8 (CCK-8), calcein/propidium iodide (PI) staining and immunostaining, we determined the OGD treatment time of 4 h, a timepoint when the cells showed a significant decrease in viability and increased protein expression of RIP3, phosphorylated RIP3 (pRIP3) and phosphorylated MLKL (pMLKL). After pretreatment with the inhibitor of RIP3, necroptotic protein expression decreased under OGD conditions, and cell necrosis decreased. Transwell assays proved that cell migration ability was retained. Furthermore, the expression of the adipogenic transcription factor peroxisome proliferator-activated receptor γ (PPARγ) and quantitative analysis of Oil Red O staining increased in the inhibitor group. The expression of vascular endothelial growth factor-A (VEGFA) and fibroblast growth factor 2 (FGF2) and the migration test suggest that OGD increases the secretion of vascular factors, promotes the migration of human umbilical vein endothelial cells (HUVECs), and forms unstable neovascularization. ELISA revealed that inhibition of RIP3 increased the secretion of the anti-inflammatory factor, interleukin (IL)-10 (IL-10) and reduced the expression of the proinflammatory factor IL-1β. Inhibition of RIP3 can reduce the death of ADSCs, retain their migration ability and adipogenic differentiation potential, reduce unstable neovascularization and inhibit the inflammatory response.